STRATEGIES CONSIDERED EFFECTIVE BY BUSINESS EDUCATORSFOR QUALITY ASSURANCE IN BUSINESS EDUCATIONPROGRAMME IN TERTIARY INSTITUTIONS IN ANAMBRASTATE (NAU Journal of Technology and Vocational Education, 2024)
This study ascertained strategies considered effective by business educators for quality assurance inbusiness education programme in tertiary institutions in Anambra State. Two research questionsguided the study and two null hypotheses were tested. Descriptive survey research design wasadopted for the study. The population comprised 117 business educators in four public tertiaryinstitutions in Anambra State. The entire population was studied without sampling because the sizewas not too large. The instrument used was 16-items structured questionnaire. The instrument wasvalidated by three experts. To determine the internal consistency, Cronbach’s Alpha was used totestthe reliability of the instrument and an overall coefficient value of 0.87 was obtained. Meanandstandard deviation were used to answer the research questions, while t-test were used to test the nullhypotheses at 0.05 level of significance. The findings of the study revealed that respondents ratedtheadministrative strategies effective for quality assurance in business education in tertiary institutions inAnambra State to a high extent while motivational to a moderate extent. The type of institutionssignificantly influenced respondents’ mean ratings on the extent administrative and motivationalstrategies were considered effective for quality assurance in business education in tertiary institutionsin Anambra State. Based on the findings, it was concluded that business education is not takenintocognizance in the country’s quest to make college and education, and university education accessibleto all; the quality of education is deteriorating as the days keep unfolding. It was thereforerecommended among others that, the entire strategies put in place for assuring quality shouldbeproperly monitored and regularly appraised by managements for effective control to achieve thedesired results
Keywords: Tertiary institutions, Strategies, Quality assurance, Business education programme